Electrochemical fabrication of FeSx films with high catalytic activity for oxygen evolution. Issue 55 (9th October 2019) - Wang, Wenbin; Xu, Ruidong; Yu, Bohao; Wang, Xuanbin; Feng, Suyang
Abstract : Electrochemical decomposition of water to produce oxygen (O2 ) and hydrogen (H2 ) through an anodic oxygen evolution reaction (OER) and a cathodic hydrogen evolution reaction (HER) is a promising green method for sustainable energy supply. Abstract : Electrochemical decomposition of water to produce oxygen (O2 ) and hydrogen (H2 ) through an anodic oxygen evolution reaction (OER) and a cathodic hydrogen evolution reaction (HER) is a promising green method for sustainable energy supply. Here, we demonstrate that cauliflower-like S-doped iron microsphere films are materials that can efficiently decompose water as an electrocatalyst for the oxygen evolution reaction. FeS x films are prepared by a simple one-step electrodeposition method and directly grow on copper foam from a deep eutectic solvent, ethaline (mixture of choline chloride and ethylene glycol), as a durable and highly efficient catalyst for the OER in 1.0 M KOH. The prepared FeS x /CF, as an oxygen-evolving anode, shows remarkable catalytic performance toward the OER with a moderate Tafel slope of 105 mV dec −1, and require an overpotential of only 340 mV to drive a geometrical catalytic current density of 10 mA cm −2 . In addition, this catalyst also demonstrates strong long-term electrochemical durability. This study provides a simple synthesis route for practical applications of limited transition metal nano catalysts.